(untitled) (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
Learners of English as a non-native anguage unavoidably confront situations in which insufficiency of their linguistic knowledge presents them with difficulties. There are also case in which the absence of some native-language lexical items in the target language is the source of problems the learners have to grapple with. This study focused on the phenomenon known as ˜lexical gap .The aim was to identify and examine the use of compensatory strategies employed by Iranian EFL students in coping with lexical gaps.To this end, number of Iranian undergraduate EFL students were selected and then split into two groups of intermediate-level and advanced-level. Both groups were given two written tasks requiring them to introduce eight Farsi words with no English counterparts to a typical native speaker of English. The analysis of data revealed well as the existence of some surprising differences between the frequencies of strategy use by the two groups.